Evaluation of the Fixation Effect of Citric Acid, Kaiserling 5% and Jores Solutions on Heart Tissue - Boduc, Erengul; Ozdemir, Bengül; Celik, Elif (Jour Med Resh and Health Sci, 2023)
Objective: By evaluating the fixation effect of citric acid, kaiserling 5% and Jores solutions on heart tissue, it was aimed to determine a suitable solution for cadaver embalming. Because nowadays, carrying out cadaver embalming with a solution that is as strong as the infection-breaking effect of formalin but also preserves color and flexibility has become one of the most important issues of the entire anatomy community. Methods: The solutions were prepared with the knowledge of the literature. The heart organs were photographed freshly with a millimetric scale on them. Three months later, the heart organs were removed from the solutions, a millimetric scale was placed on them again and they were photographed. In addition, the solutions were examined microbiologically every week. Three months later, after photographs were taken, histological examination was performed on sections taken from three heart tissues. Results: As a result of color measurements, it was observed that the color was preserved best in Jores solution. In histological examination, it was determined that cell and tissue integrity was best preserved in Kaiserling 5% solution. But Jores solution also gave results close to 5% Kaiserling solution in histological examination. In the microbial analysis, no gram (+) and gram (-) bacteria were detected in all three solutions. Additionally, the solutions are good in that they do not cause yeast growth within three months in the room temperature. Conclusion: Cadaver embalming solutions are becoming more and more important day by day.Considering the results obtained, the microbial, histological and color preservation effects of Kaiserling 5% solution can be disseminated as a cadaver embalming solution. In addition, it has been revealed that the Jores solution gives similar results to the Kaiserling 5% solution. Taking anatomy laboratory courses in a cadaver environment embalmed with a solution that does not smell of formalin and has no irritating effects will greatly affect the course quality and learning.